Konfiks Ke-an dalam Bahasa Indonesia - Dewi Herlina; Siti Sulistiyarini (SPHOTA: Jurnal Linguistik dan Sastra, 2024)
This research aims to describe the circumfix "ke-an" in the Indonesian language, focusing on its phonological changes, grammatical functions, and meanings. The data were taken from excerpts from the novel "Negeri Para Bedebah" by Tere Liye and sentences created by the researcher as a native speaker of the Indonesian language. The researcher used distribution and paraphrasing methods to address the research questions. Based on the research results, three phonological change rules were found in forming the circumfix "ke-an" from its base form to a polymorphemic word. The allomorphs are "ke-yan," "ke-wan," and "ke-Ɂan." In terms of its grammatical function, the circumfix "ke-an" was examined both derivationally and inflectionally. Based on its grammatical meaning, the circumfix "ke-an" can express at least four things, namely, expressing abstract concepts, indicating a place, indicating suffering, and indicating quality.